All’s Well That Ends Well: A Review of Indonesian State Owned Enterprise’s Organizational Culture - Antoni Ludfi Arifin; Resista Vikaliana; Wahyuddin Latunreng (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Corporate culture consists of values, beliefs and standards that influence the thoughts and behavior of people in the company and are the key factors used to describe corporate culture. In Indonesia, on July 1, 2020, has inaugurated and established the AKHLAK cultural value as the main principle and value (core value) of every State Owned Enterprise (SOE).  The AKHLAK cultural value is a behavioral guide in achieving the company's vision, namely Amanah, Competent, Harmonious, Loyal, Adaptive, and Collaborative. This study aims to see the extent to which the implementation of AKHLAK values in Indonesian SOEs. Systematic Literature Review method is used in this research by searching articles in international journal databases. The results of the study underline that there are only 3 articles that highlight the study of organizational culture in Indonesian SOEs and only 1 article that examines the core value of AKHLAK.  Therefore, research on core values in Indonesian SOEs still has a great opportunity to be researched in the future.